2004
DOI: 10.1080/09291010412331313313
|View full text |Cite
|
Sign up to set email alerts
|

Using Covariance to Unravel the Effects of Meteorological Factors and Daily and Seasonal Rhythms

Abstract: Many factors contribute to the activity of animals in the wild. Whilst daily and seasonal rhythms are likely to be present, and to represent underlying biological functions, these will normally be modified by several factors in the environment. Important amongst these are light, temperature, humidity and whether or not it is raining. There is also the problem that the factors might interact, the effect of, say, time of day, being modified by the concomitant temperature. Separating out the effects of these diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The species of Meliponini studied did not leave the nest before the temperature reached 19°C, but for M. scutellaris acrophase times generally occurred when the average temperature was around 24°C and the acrophases of F. doederleini occurred at higher temperature values (average 27°C). Similar results have been obtained for Frieseomelitta flight activity in other localities, such as in Ribeirão Preto (São Paulo State) in a study of F. doederleini (under laboratory controlled conditions) (Almeida, 2004) and of F. varia (under field conditions) (Nevill et al, 2004). Furthermore, positive correlation between bee activities of nest entrance with and without pollen and tempera-of nest entrance with and without pollen and tempera-and temperature may be observed in the studies of Souza et al (2006), in relation to M. asilvai in Pedra Branca.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The species of Meliponini studied did not leave the nest before the temperature reached 19°C, but for M. scutellaris acrophase times generally occurred when the average temperature was around 24°C and the acrophases of F. doederleini occurred at higher temperature values (average 27°C). Similar results have been obtained for Frieseomelitta flight activity in other localities, such as in Ribeirão Preto (São Paulo State) in a study of F. doederleini (under laboratory controlled conditions) (Almeida, 2004) and of F. varia (under field conditions) (Nevill et al, 2004). Furthermore, positive correlation between bee activities of nest entrance with and without pollen and tempera-of nest entrance with and without pollen and tempera-and temperature may be observed in the studies of Souza et al (2006), in relation to M. asilvai in Pedra Branca.…”
Section: Discussionsupporting
confidence: 84%
“…When studying the Trigona mosquito (=Plebeia mosquito) (Smith), Lutz (1931) observed that light intensity interfered at the beginning and end of daily activities. Further-Furthermore, in Ribeirão Preto (SP), Nevill et al (2004) confirmed that this abiotic factor had a positive influence on the external activities of F. varia. According Corbet et al (1993) the daily activities of social bees would start at sunrise and would be more correlated with light intensity than the temperature.…”
Section: Discussionmentioning
confidence: 66%
“…While observations in the lab can bring important insights into the biology of individual species, they cannot supplement observations in the field, where the complexity of the ecosystem is influenced by species interactions and the unpredictability of the environment Nevill et al 2004). Thus, activity rhythms of animals can be masked by factors like food availability (Fernandéz de Miguel and Aréchiga 1994), changes in water masses DO concentrations (Schurmann et al 1998;Matabos et al 2011).…”
Section: Species Assemblage Structure and Environmental Influencementioning
confidence: 99%
“…Thus, activity rhythms of animals can be masked by factors like food availability (Fernandéz de Miguel and Aréchiga 1994), changes in water masses DO concentrations (Schurmann et al 1998;Matabos et al 2011). The need to statistically separate the effect of meteorological factors and activity rhythms was recognized by Nevill et al (2004). His method allows one to determine how species activity covary with changing environmental conditions but is not applicable at the system level when dealing with a multispecies assemblage to understand ecosystem dynamics as whole.…”
Section: Species Assemblage Structure and Environmental Influencementioning
confidence: 99%